Analisa Pengaruh Objek Spasial Terhadap Harga Sembako Di Kota Bandung - Seno Anunggroho; Kiki Adhinugraha; Ibnu Asror (eProceedings of Engineering, 2017)
This research discusses the analysis of influence of spatial object that exists around the market in Bandung against the price of basic food. To determine the required price data analysis is complete food prices, Basic food data obtained from the Office of Industry and Trade of West Java and will only take sampling from 5 markets in the city of Bandung that is Kiara Condong Market, Baru Market, Sederhana Market , Andir Market Dan Kosambi Market. The theory to be used in this research is Iterative Dichotomiser 3 one of theory from decision tree,the author use this method because the decision tree can find hidden relationships or patterns between variables .With this analysis we can know how the influence of the object on the price of basic food in the city of Bandung.Kata Keyword : Decision Tree, ID3,Basic Food